Pengaruh Money Attitude, Financial Knowledge Dan Financial Self Efficacy, Terhadap Financial Management Behavior Mahasiswa S-1 Universitas Sebelas Maret - Ilmi Ghaniya Rahayu; Aniek Hindrayani; Salman Alfarisy Totalia (Universitas Negeri Surabaya, 2023)
This study aimed to examine the effect of money attitude, financial knowledge, and financial self-efficacy on financial management behavior of undergraduate students of Sebelas Maret University. This research was a quantitative descriptive study with 395 respondents as research subjects. They were undergraduate students of Sebelas Maret University. The sampling technique was carried out using a probability sampling technique with a proportionate stratified random sampling. Data was collected through a questionnaire distributed via the Google form link. The data validity test employed the CFA technique. The data analysis used multiple regression analysis. The results obtained were as follows. First, money attitude had a positive and significant effect on the financial management behavior of undergraduate students. Second, financial knowledge had a positive and significant effect on the financial management behavior of undergraduate students.Third, financial Self Efficacy had a positive and significant effect on the financial management behavior of undergraduate student.